FEMALE SUBALTERNITY IN HANNA RAMBE'S NOVEL MIRAH DARI BANDA - Ainur Rahman; Rahmad, Rahmad; Tauhed Supratman, Muhammad (Universitas Negeri Yogyakarta, 2023)
Subaltern reading begins with an author's view of the conditions that characterize subaltern groups. Subaltern falls within the realm of postcolonial feminism which is a form of alliance between postcolonial theory and feminism, seeks to beat back existing gender, cultural, or racial hierarchies, and rejects binary opposition to patriarchalism or colonialism's constructs of authority. This research tries to reveal the subalternity of women during colonialism in the novel Mirah dari Banda. The method used in this research is descriptive qualitative, namely by examining texts that contain subaltern elements. The data in this study are in the form of text sentences or dialogues that reflect subaltern women due to the domination of colonialism. The findings of this study that there are several forms of subaltern experienced by indigenous women (Mirah), including degrading dignity, sexual harassment, physical/verbal violence, obedience to the invaders, and control over others. From some of the research findings, subaltern women do not have a conceptual language to fight against colonial groups or indigenous men, and also women do not have the power to carry out resistance to the hegemonic power of groups in power.